Pre-Service Physics Teacher Conceptions and Visual Literacy to Observe Sky Maps throught Heaven View Media - Susilawati Susilawati; Dadi Rusdiana; Ida Kaniawati; Taufik Ramlan Ramalis (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
Learning science, especially learning astronomy subjects, is still very limited in activities carried out by students. The observation of the sky map provided is adequate as a learning media that can support student curiosity and concept understanding of stars for students. The research aims to explore the relationship between students 'conceptions of the stars using a sky map application, students' perceptions of Heaven Above media and visual literacy in the implementation of learning astronomy courses. Research participants involved 72 students who took astronomy lessons. The instrument consisted of a observation sheet and a questionnaire that had gone through the construct and content validation process. Data analysis using quantitative analysis factor analysis and determines normalized gain to descripe an increase in student visual literacy of stargazing. In addition, the calculation of the proportion questionnaire for students 'conceptions of learning and students' perceptions of the heaven view application then analyzes the factors to show the correlation. The result of this research is understanding that a deeper understanding of the concept and experience of maps is a need of students who can support the learning community in learning to observe more interesting stars. Visual literacy has increased between twice observation.